Effects of walking on quality of life (QOL) of mastectomy patients in hospitals of Tehran - Moshtagh Eshgh, Z; Rahemi, Z; Yaghmaei, F; Alavi Majd, H (Advances in Nursing & Midwifery, 2010)
Background and Aim Breast cancer is the most common malignancy in women with an estimated new cases amount to 178000 in 2007. Although surgery is the most frequent intervention, patients experience problems both from the disease and from surgery, leading to negative impact on their quality of life (QOL). Accordingly, such exercises as walking can improve their QOL. The aim of this quasi-experimental one-group study was to assess the effect of walking on QOL of mastectomy patients in 2007. Materials and Methods 34 subjects selected by purposive and convenience sampling methods took part in the study. A two-part questionnaire including demographic as well as QOL items and a self-report form were used for data collection. After determining content and face validities, the reliability of the questionnaire was figured by internal consistency (α=0.89) and test-retest (r=0.91) methods. Walking was performed in a flat area, 3 times a week and each time 30 minutes over 6 weeks. QOL items in the questionnaire were completed 2 times before and after the intervention. Findings Mean scores of physical domain before and after the intervention were %64.55±8.10 and 78.89±5.81, of psychological domain 52.89±10.74 and 64.92±8.64, of social domain 64.76±9.59 and 79.06±25.62, of economical domain 68.63±16.29 and 73.28±15.32 and of spiritual domain 79.96±12.57 and 82.54±11.18 respectively. Mean scores of total QOL were 66.16±6.30 and 75.74±6.59 before and after the intervention respectively. A significant increase was found in all domains except spiritual. Conclusion It can be concluded that walking has positive effects on QOL of mastectomy patients to overcome their problems. Keywords: Walking, Quality of life (QOL), Mastectomy. *Corresponding Author: Moshtagh Eshgh, Z. Lecturer, Dept. of Medical-Surgical Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. E-mail: z.moshtagh@yahoo.com